Impact of water availability on food security in GCC: Systematic literature review-based policy recommendations for a sustainable future - Lara G. Moussa (20484047) (2024)
Despite being the most food-secure region among Arab countries, the Gulf Coordination Council (GCC) region is predicted to face challenges in food security. The study aimed to develop evidence-based policy recommendations to promote sustainable water use, enhance agricultural productivity, and ensure food security in the GCC countries. Using a systematic literature review approach, we examined 64 peer-reviewed articles (2010–May 2024) focused on the impact of water availability in enhancing the GCC regions’ food security. The GCC region faces severe challenges in water availability due to its hyper-arid climate, depleting non-renewable groundwater reserves, rapid urbanization, climate change impacts, and population growth, highlighting the need for efficient and sustainable water management. Innovative strategies have enabled efficient water management in the GCC region, facilitating food production (i.e., subsurface drip irrigation, variable rate irrigation, deficit irrigation strategy, desalination plants, and wastewater treatment plants). Source markets and supply chain disruptions have motivated the GCC countries to impose policy recommendations to enhance food security (i.e., controlled water discharge, crop suitability assessments, proper water management practices, shifting to drought-tolerant crops, and leveraging virtual water trade). Such implementations should be further researched based on expert scientific contribution and collaborative efforts facilitated via increased funding and resources. Political differences among GCC countries have created challenges in developing collaborative efforts in food production. Based on our systematic review, we have outlined policy recommendations to secure water availability for food production in the GCC region. We emphasize the importance of promoting research and development, addressing socio-economic barriers, and enhancing data-driven decision-making as pivotal strategies for sustainable water management and agricultural resilience. Other Information Published in: Environmental Development License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.envdev.2024.101122